Length of hospital stay analysis. Simultaneous laparoscopic surgery in treatment of combined surgical pathology of organs of abdominal cavity - Halei, M.; Dzubanovskyi, I.; Marchuk, I. (Journal of Education, Health and Sport, 2020)
Length of stay is one of the most evident indexes in evaluation of efficiency and expediency of treatment methods. It is useful to exploit it to compare different approach of treatment of the same pathology. Aim of our work was to analyze effectiveness of simultaneous operations for treatment surgical pathology of organs of abdominal cavity and gallstone disease. To compare the results of simultaneous treatment with results of classical treatment. We used statistics formed of 1157 patients that underwent operations in minimal invasive surgery unit of Volynian regional clinical hospital (Lutsk,Ukraine) in period of 2013-2019 years. Patients were divided into two groups. The research group (Group 1) was formed by 411 patient that underwent simultaneous laparoscopic surgery for treatment of gallstone disease and combined surgical pathology of organs of abdominal cavity. The control group (Group 2) was formed by 746 patients that underwent mono laparoscopic operation for treatment only one pathology of abdominal cavity. Groups were compared using such indexes as length of stay, number of conversions, number of complications, time of the operation. In the result terms of hospital stay were 3.52 days in group 1 and 3.55 days in group 2. Conversion was performed in 0.48% of patients in group 1 vs. 0.4% in group 2. Number of intraoperative complications was 1.93% in research group vs 2.14% in control. Time of operation was longer in group 1 vs group 2 up to 20% due to bigger volume of operation. The difference was smaller than operation itself. There were no operations that continued longer than 2 hours. Simultaneous operations are more effective because of its` suitability for combined pathology with no need for repeat hospitalization and operation. Simultaneous operations are as safe as standard mono operation.